Inverse Association of Circulating SIRT1 and Adiposity: A Study on Underweight, Normal Weight, and Obese Patients - Mariani, Stefania; di Giorgio, Maria R.; Martini, Paolo; Persichetti, Agnese; Barbaro, Giuseppe; Basciani, Sabrina; Contini, Savina; Poggiogalle, Eleonora; Sarnicola, Antonio; Genco, Alfredo; Lubrano, Carla; Rosano, Aldo; et al. (Frontiers in Endocrinology, 2018)
Context: Sirtuins (SIRTs) are NAD+-dependent deacetylases, cellular sensors to detect energy availability and modulate metabolic processes. SIRT1, the most studied family member, influences a number of tissues including adipose tissue. SIRT1 reduces its activity with weight gain and becomes activated in conditions of starvation. Objective: To focus on SIRT1 plasma concentrations in different conditions of adiposity and to correlate SIRT1 with fat content and distribution, energy homeostasis and inflammation in under-weight, normal-weight and obese individuals. Material and methods: 21 patients with anorexia nervosa, 26 normal-weight and 75 patients with obesity were evaluated. Body fat composition by dual-energy X-ray absoptiometry, ultrasound liver adiposity, echocardiographic epicardial fat thickness (EFT), inflammatory (ESR, CRP, and fibrinogen) and metabolic (FPG, insulin, LDL- and HDL-cholesterol, triglycerides) parameters, calculated basal metabolic rate (BMR) and plasma SIRT1 (ELISA) were measured. Results: SIRT1 was significantly higher in anorexic patients compared to normal-weight and obese patients (3.27±2.98, 2.27±1.13 and 1.36±1.31 ng/ml, respectively). Linear regression models for each predictor variable adjusted for age and sex showed that SIRT1 concentration was inversely and significantly correlated with EFT, fat mass %, liver fat content, BMR, weight, BMI, WC, LDL-cholesterol, insulin, ESR. Step-wise multiple regression analysis revealed that age and EFT were the best independent correlates of SIRT1 (β=-0.026, p = 0.025 and β=-0.516, p<0.001, respectively). Conclusions: Plasma SIRT1 shows a continuous pattern that inversely follows the whole spectrum of adiposity. SIRT1 significantly associates with EFT, a strong index of visceral fat phenotype, better than other indexes of adiposity studied here.